ACTIVITY OF YOUNG PEOPLE WITH DISABILITIES IN THE DIGITAL ENVIRONMENT - Usca, Svetlana; Vindece, Aija (Education Reform: Education Content Research and Implementation Problems, 2020)
Young people with disabilities are often socially inactive because their participation in social and economic processes is limited. In order to reduce this, digital technologies are important, the use of which allows any individual to engage in various types of activities (educational, cultural, economic, etc.).Objective of the paper: to analyze the results of exploratory research on the activity of young people with disabilities in the digital environment. Methods: questionnaire, focus discussion.The results suggest that support and education measures require a differentiated approach, in which it is important to determine the level of interests and digital competence of each young person with disabilities, clearly set goals that can be adapted to individual needs, tasks according to individual abilities/skills. This means working in small groups or individually.